Synthesis and biological evaluation of thiazole and metergoline derivatives as antimycobacterial and antiplasmodial agents - Mjambili, Faith Riziki (Department of Chemistry, 2014)
TB patients show poor compliance to available drugs due to the costs, adverse side effects, and prolonged treatment, leading to multi-drug resistant (MDR), extensively drug resistant (XDR), and most recently totally drug resistant TB. Shared drug toxicities and drug interactions with antiretrovirals compound the problem. The rapid development of resistance to known antimalarials compared to the rate at which new agents are coming into the market still remains a big challenge is combating malaria. Currently, with resistance to ACTs having been documented in South-East Asia, the situation is dire as there is no ready alternative to these drugs. There is thus a heightened need for research towards the development of new anti-TB and anti-malarial drugs based on novel chemotypes. Towards addressing this need, SAR studies were conducted on the 2-amino-4-aryl thiazole scaffold by synthesizing a series of derivatives with different motifs at the various positions of the scaffold. These derivatives exhibited moderate antiplasmodial activity in the CQS strain of P. falciparum, and good antimycobacterial activity on the H37Rv strain of M.tb. A 2-pyridyl group at position 4 of the thiazole ring as well as a substituted phenyl at position 2 was found to be essential for antimycobacterial activity. However, the 2-pyridyl group was not essential for antiplasmodial activity while the substituted phenyl at position 2 was essential for antiplasmodial activity. The linker between these two groups affected antimycobacterial activity with little influence on the antiplasmodial activity. In addition structural modifications were performed on the ergoline backbone of metergoline, and a number of derivatives synthesized with different para substituted phenyls. These compounds exhibited moderate antiplasmodial activity in the CQS strain of P. falciparum, and moderate antimycobacterial activity on the H37Rv strain of M.tb. The presence of a substituted phenyl group attached to the nitrogen atom of the amine was found to be essential for antimycobacterial activity, however, this substituted phenyl group didn't confer optimum antimycobacterial activity as the compounds were less active than metergoline. The antiplasmodial activity of these compounds was better than that of metergoline and was enhanced by the hydrophobicity of the substituent on the phenyl ring. Changing the linker between the ergoline backbone and the substituted phenyl ring didn't have any significant effect on either the antimycobacterial or the antiplasmodial activity.